Instrumentation and methods for the complex investigations of swimming - Boicev, K.; Tzvetkov, A. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
Methodology of scientific research in the field of physical. culture and especially in sports is relatively underdeveloped. This is understandable since it is a very young area. Consequently, it is necessary to improve it, particularly regarding the study of specific movements and training programs of competitors. It is also important to study the competitors' physical charac· teristics so they can be classified and graded relative to their performance. The practice of conducting pure laboratory experiments has to be gradually directed to investigations of sportsmen in the practical setting. In testing the athlete's condition before and after training, it is necessary to determine the reaction and the effectiveness of the applied work during his performance. To evaluate his condition, the single method of analysis commonly used must be replaced by more complex techniques. All this is in connection with the urgent need for gaining greater knowledge about the requirements of different disciplines, developing greater perfection in the specific utilization of the methods, and ensuring higher effectiveness and rationale for training. In short, this leads to a more complete understanding of the entire sport activity and makes possible greater efficiency.